WHATSAPP PUSH NOTIFICATION INFORMATION SYSTEM ON PLN ICON PLUS WEBSITE-BASED INTERNET SERVICES USING THE RAPID APPLICATION DEVELOPMENT (RAD) METHOD - Wardana, M Aji; Elhanafi, Andi Marwan (Cattleya Darmaya Fortuna, 2025)
The development of Information technology has had a significant impact on various aspects of life, including time and Information management. One crucial aspect is an effective and efficient Notification management system, where timely and relevant notifications are essential to support activities in various contexts, both personal, business, and organizational. This study discusses the design and development of a WhatsApp-based Notification Information System to improve internet services at PT PLN Icon Plus. This system is designed to accelerate and facilitate the delivery of information related to disruptions or maintenance of internet services to customers. The method used is Rapid Application Development (RAD), which allows the application development process to be faster and more flexible to changes in user needs. The result of this study is a prototype of an automatic notification system that can send WhatsApp messages directly to customers, thus supporting the creation of more effective and responsive communication between the company and customers. With this system, it is hoped that the quality of PT PLN Icon Plus internet services will increase and customer satisfaction can be maintained.